2012
DOI: 10.1055/s-0032-1323680
|View full text |Cite
|
Sign up to set email alerts
|

CCAAT/Enhancer-binding Protein-Homologous Protein Sensitizes to SU5416 by Modulating p21 and PI3K/Akt Signal Pathway in FRO Anaplastic Thyroid Carcinoma Cells

Abstract: SU5416, vascular endothelial cell growth factor receptor inhibitor, suppresses hypoxia-induced angiogenesis, growth, proliferation, and metastasis in cancer cells. CCAAT/enhancer-binding protein-homologous protein (CHOP) has pivotal roles in regulation of growth and survival. In the present study, we evaluated the effects of SU5416 on cell survival, p21, and PI3K/Akt signal pathway in FRO anaplastic thyroid carcinoma (ATC) cells. Moreover, we investigated the roles of CHOP in cell survival under condition of S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
8
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 7 publications
1
8
0
Order By: Relevance
“…Based on our results for p21 and Akt, it is proposed that increased p21 expression and unchanged Akt activity constitute the phenotype of resistance to SU6656-induced cell death in FRO ATC cells. Considering that both SFK inhibition (the present study) and VEGFR inhibition (our previous report) magnify their cytotoxic eff ects on FRO ATC cells through regulation of p21 and PI3K/Akt signaling, it would seem that manipulation of p21 and PI3K/Akt signaling potentiates the therapeutic efficacy of SFK inhibitors and VEGFR inhibitors in ATC [ 23 ] . PI3K/Akt signaling regulates survival in harmony with p21 [ 37 ] .…”
supporting
confidence: 53%
See 4 more Smart Citations
“…Based on our results for p21 and Akt, it is proposed that increased p21 expression and unchanged Akt activity constitute the phenotype of resistance to SU6656-induced cell death in FRO ATC cells. Considering that both SFK inhibition (the present study) and VEGFR inhibition (our previous report) magnify their cytotoxic eff ects on FRO ATC cells through regulation of p21 and PI3K/Akt signaling, it would seem that manipulation of p21 and PI3K/Akt signaling potentiates the therapeutic efficacy of SFK inhibitors and VEGFR inhibitors in ATC [ 23 ] . PI3K/Akt signaling regulates survival in harmony with p21 [ 37 ] .…”
supporting
confidence: 53%
“…There is report that p21 expression decreases in PTC cells with a tendency to undergo early metastasis and another one that p21 expression is not correlated with clinicopathological factors in PTC tissues [ 15 , 32 ] . We found that p21 is associated with resistance to cell death in VEGFR inhibitor-treated FRO ATC cells [ 23 ] . Meanwhile, proteasome inhibitor and epigallocatechin-3-gallate cause cell death in ARO colon cancer cells by increasing p21 levels, and PPARγ agonist exerts an antiproliferative eff ect in ARO colon cancer cells and DRO melanoma cells by increasing p21 levels [ 16 -18 , 33 ] .…”
mentioning
confidence: 64%
See 3 more Smart Citations